Family background and contemporary changes in young adults' school-work transitions and family formation in the United States. (December 2016) - Smith, Chelsea; Crosnoe, Robert; Chao, Shih-Yi
Highlights: Youth are less likely to acquire adult roles by age 32 today than 20 years ago. Cross-cohort delays in school completion were driven by disadvantaged youth. Cross-cohort delays in employment and childbearing were driven by advantaged youth. Cross-cohort differences in marriage did not vary by family background. Abstract: The oft-discussed lengthening of the transition into adulthood is unlikely uniform across diverse segments of the population. This study followed youth in the National Longitudinal Survey of Youth 1979 and 1997 cohorts ( n = 12, 686 and 8, 984, respectively) from 16 to 32 years old to investigate this trend in the United States, examining cross-cohort changes in transitions with a focus on differences by family background. Logistic regressions revealed that young adults in the most recent cohort were less likely to have completed schooling, fully entered the labor force, married, or become parents by their 30s than those in the older cohort. The cross-cohort drop in young adults completing schooling was more pronounced among youth from more disadvantaged family backgrounds, the drop in entering the labor force and having children was more pronounced among those from more advantaged backgrounds, and the drop in marriage did not differ by family background.